Io puro, io reale e storicità immanente del soggetto: A partire dal Bleistiftmanuskript (1912) di Husserl - Pugliese, Alice (B@belonline, 2020)
The so-called Bleistiftmanuskript (Pencil Manuscript), dating from the period between October and December 1912, is one of the three Urtexte from which the new critical edition of Husserl’s Ideas II has been elaborated. This text faces us with the problem of the relationship between the pure I and consciousness starting from a conception of consciousness itself as predominantly obscure. The article reconstructs this relationship as a dynamic between Aktvollzug (act-achievement) and Entfremdung (alienation) trying to give an account of the status of the real (reel) self in its relationship with material things and the body. In conclusion, the notion of a specific ‘historical vulnerability’ of the subject is outlined.